DETERMINATION OF THE REACTION RATE CONSTANT FOR THE INTERACTION OF DIETHYL SULFOXIDE WITH THE HYDROXYL RADICAL ON THE BASIS OF COMPETITIVE KINETICS (Proceedings of the YSU B: Chemical and Biological Sciences, 2018)
In the paper, radical scavenging property of diethyl sulfoxide towards hydroxyl radical with the use of competitive reaction kinetics has been investigated. The obtained results confirm that diethyl sulfoxide compared with dimethyl sulfoxide has a greater ability to capture OH radical.
Keywords: diethyl sulfoxide, dimethyl sulfoxide, hydroxyl radical, UV radiation, 4,4-dimethyl-4-nitrosoaniline, rate constant